Getting a foot in the door: how organisational characteristics shape recruitment decisions in the dual apprenticeship system - Protsch, Paula [Verfasser] (My University, 2017)
"Employers' recruitment behaviour in entry labour markets is central for young people's transitions from school to work. Whereas previous research has focused on the effects of specific applicant characteristics, I concentrate on how organisational characteristics, namely organisation size and private or public sector affiliation, relate to selection decisions in the dual apprenticeship system in Germany which is a major entry labour market. Following organisational and institutional theory, I expect early selection stages to be more open at larger and public organisations in contrast to smaller private organisations. I also investigate how different organisations respond to school grades as applicants' signals of skills. I use field experiment data combining organisational-level and applicant-level data to analyse how actual employer responses to written applications by fictitious young people vary with organisation type. The results indicate that, net of applicant characteristics and occupation-specific practices, applications are more likely to receive an invitation to a follow-up selection stage if submitted to larger organisations, and especially larger public organisations, rather than to smaller private organisations. This finding extends to applicants with poorer school grades. Public sector affiliation, however, did not seem to matter much within the group of smaller organisations." (author's abstract; BIBB-Doku)
Keywords: G 1.3.2.2 Übergänge; S 5.3 Personalentwicklung; S 3.2 Unternehmen und Behörden; Berufseinmündung; Erste Schwelle; Ausbildungsstellenmarkt; Personalgewinnung; Personalauswahl; Ausbildungsverhalten; Organisation; Privatwirtschaft; Öffentlicher Dienst